The role of single parents in developing children’s self-awareness; A case study in the Islamic region, Aceh - Muthmainnah, Muthmainnah; Amelia, Lina; Safira, Rahma; Faisal , Muhammad (Atfaluna: Journal of Islamic Early Childhood Education, 2024)
This study aims to analyze the steps single parents take in fostering the self-awareness of 5-year-old children and describe their attitudes. This qualitative research used a case study approach that involved two single parents and two children aged five years as research subjects. Based on interviews and observations, single parents foster children's self-awareness through several steps: recognizing one's own emotions and the emotions of others, managing one's emotions, motivating oneself, being a role model, and building social relationships. As a result, children's self-awareness manifests in self-confidence, independence in choosing activities, emotional control, understanding of rules, discipline, persistence, and pride in their work. The development of self-awareness in 5-year-old children is closely related to the steps implemented by single parents, with being a role model being the most effective method in fostering children's self-awareness.